Smudge cells due to infectious mononucleosis. (2021) - Higuchi, Toru; Eiki, Ogawa; Hiroshi, Hamashima; Kenta, Ito
Abstract: The smudge cells are well studied as a prognostic factor for chronic lymphocytic leukemia, but it is also found in viral infections. We experienced a case of abnormal hyperleukocytosis (WBC 41, 600/mm3) associated with infectious mononucleosis (IM). The smudge cells were observed in peripheral blood smears, and were counted by mistake for the normal lymphocytes by the automatic blood count meter.